2013
DOI: 10.1051/0004-6361/201322320
|View full text |Cite
|
Sign up to set email alerts
|

Strongly star-forming rotating disks in a complex merging system atz= 4.7 as revealed by ALMA

Abstract: We performed a kinematical analysis of the [CII] line emission of the BR 1202-0725 system at z ∼ 4.7 using ALMA science verification observations. The most prominent sources of this system are a quasar (QSO) and a submillimeter galaxy (SMG), separated by a projected distance of about ∼24 kpc and characterized by very high star formation rates, higher than ∼1000 M yr −1 . However, the ALMA observations reveal that these galaxies apparently have undisturbed rotating disks, which is at variance with the commonly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 99 publications
(204 reference statements)
12
92
2
Order By: Relevance
“…This means that large, settled-down, 10 kpc-scale galaxy disks cannot be in place much before z = 2. Our size measurements of the HDF 850.1 north and south objects are consistent with these ideas, as are the recent measurements of kpc-sized rotating molecular disks in BR1202-07-NW and SE at z = 4.7 (Salomé et al 2012;Carniani et al 2013). The infalling gas does have time to establish rotational support in kpc-scale disks by z = 5, but not in the order-of-magnitude larger disks that may be in place by z = 2.…”
Section: Conclusion: Hdf 8501 Is Similar To Other High-z Ulirg and Ssupporting
confidence: 89%
“…This means that large, settled-down, 10 kpc-scale galaxy disks cannot be in place much before z = 2. Our size measurements of the HDF 850.1 north and south objects are consistent with these ideas, as are the recent measurements of kpc-sized rotating molecular disks in BR1202-07-NW and SE at z = 4.7 (Salomé et al 2012;Carniani et al 2013). The infalling gas does have time to establish rotational support in kpc-scale disks by z = 5, but not in the order-of-magnitude larger disks that may be in place by z = 2.…”
Section: Conclusion: Hdf 8501 Is Similar To Other High-z Ulirg and Ssupporting
confidence: 89%
“…Walter et al (2009) derived a source size of ∼ 1.5 kpc, and suggested that the galaxy was undergoing an Eddington-limited starburst event. Similar compact sizes were derived for two z ∼ 4 quasar host galaxies by Gallerani et al (2012) and Carniani et al (2013), who also detected companion galaxies potentially due to merge with the quasar host. Carniani et al (2013) and Wang et al (2013a) displayed the power of using ALMA to examine the dynamics of [CII]-emitting gas in quasar host galaxies, and showed that a number of galaxies in their sample potentially exhibited rotating gas disks.…”
Section: [Cii] Morphologies and Dynamicssupporting
confidence: 84%
“…Similar compact sizes were derived for two z ∼ 4 quasar host galaxies by Gallerani et al (2012) and Carniani et al (2013), who also detected companion galaxies potentially due to merge with the quasar host. Carniani et al (2013) and Wang et al (2013a) displayed the power of using ALMA to examine the dynamics of [CII]-emitting gas in quasar host galaxies, and showed that a number of galaxies in their sample potentially exhibited rotating gas disks. This all said, there have been a number of notable non-detections of [CII] at high-z that have called into question the reliability of [CII] as a gas tracer in high-z galaxies.…”
Section: [Cii] Morphologies and Dynamicssupporting
confidence: 84%
See 1 more Smart Citation
“…It is therefore a good tracer of the gas dynamics in high-redshift galaxies (e.g., Carniani et al 2013;Capak et al 2015). Only ALESS 73.1 and UDS 47.0 have lowresolution observations from Cycle 0/1 deep enough to allow us to search for possible velocity gradients.…”
Section: Velocity Gradients and Dynamical Massesmentioning
confidence: 99%